PARADIGMA TEOTERIS THE LIVING CONSTITUTION DAN PENGAKUAN HAK KONSTITUSIONAL MASYARAKAT HUKUM 400 ADAT DI INDONESIA - Windi Hikma Ardiani (UNISSULA, 2015)
This article illustrates that in a pluralistic country like Indonesia, the constitution should reflect the character and social practices that respect diversity in society. The inclusion of conditionalities in the recognition of indigenous people against the original intent of the Founding Fathers, as it should be abolished. Main problem is the existence of indigenous people, indigenous rights, and constitutional position of indigenous people themselves. Protection of the rights of indigenous people is not limited to the formulation of a precise definition of what and who’s indigenous people, but rather to formulate more clearly the position of political subdivisions in the life of the nation as a whole.